Qualitative assessment of 27 current-use pesticides in air at 20 sampling sites across Africa - Fuhrimann, Samuel; Klánová, Jana; Přibylová, Petra; Kohoutek, Jiři; Dalvie, Mohamed Aqiel; Röösli, Martin; Degrendele, Céline (Chemosphere, 2020)
Increasing use of current-use pesticides (CUPs) in Africa raises environmental and public health concerns. But there is a large uncertainty about their occurrence and the composition of pesticide mixtures on this continent. This paper investigates the presence of 27 CUPs in air across 20 sampling sites in Africa. 166 passive air samples, consisting of polyurethane foam (PUF), were collected in 12 African countries between 2010 and 2018. Samples were extracted with methanol and analyzed via high-performance liquid chromatography coupled with tandem mass spectrometry. The detection frequencies of CUPs per site were compared to land use patterns and sampling years, while their similarities were assessed using hierarchical cluster analysis. Overall, 24 CUPs were detected at least once. In 93% of all samples, at least one CUP was detected, while 78% of the samples had mixtures of two or more CUPs (median 3, interquartile range 5). Atrazine and chlorpyrifos were detected in 19 out of 20 sampling sites. Carbaryl, metazachlor, simazine, tebuconazole and terbuthylazine had the highest detection frequencies at sampling sites dominated by croplands. Across all the sampling years, 16 CUPs were present. Seven CUPs were newly detected from 2016 onwards (azinfos-methyl, dimetachlor, chlorsulfuron, chlortoluron, isoproturon, prochloraz and pyrazon), while metamitron was only present before 2012. Sites within a radius of about 200 km showed similarities in detected CUP mixtures across all samples. Our results show the presence of CUP mixtures across multiple agricultural and urban locations in Africa which requires further investigation of related environmental and human health risks.
Keywords: atrazin; pesticidy; Humans; Polyurethanes; Environmental Monitoring; Agriculture; lidé; Air Pollutants; Chlorpyrifos; Air; Pesticides; Africa; Current-use pesticides; látky znečišťující vzduch; monitorování životního prostředí; zemědělství; Afrika; polyurethany; Spatial variations; dursban; Atrazine